2020
DOI: 10.1007/s10653-020-00637-9
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals contamination in groundwater and implications on human health: comprehensive assessment using hydrogeochemical and geostatistical methods

Abstract: Monitoring the groundwater chemical composition and identifying the presence of pollutants is an integral part of any comprehensive groundwater management strategy. The present study was conducted in a part of West Tripura, northeast India, to investigate the presence and sources of trace metals in groundwater and the risk to human health due to direct ingestion of groundwater. Samples were collected from 68 locations twice a year from 2016 to 2018. Mixed Ca–Mg–HCO3, Ca–Cl and Ca–Mg–Cl were the main groundwate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…The higher concentration of Fe causes stomach irritation and enhances the iron bacterium that influences the taste of water (Brindha et al 2020). The concentration of Mn in groundwater varied from 0.055 to 0.41 mg/L (mean = 0.123 mg/L) before lockdown, and from 0.03 to 0.40 mg/L (mean = 0.113 mg/L) after COVID-19 lockdown period.…”
Section: Heavy Metals In Groundwatermentioning
confidence: 99%
See 1 more Smart Citation
“…The higher concentration of Fe causes stomach irritation and enhances the iron bacterium that influences the taste of water (Brindha et al 2020). The concentration of Mn in groundwater varied from 0.055 to 0.41 mg/L (mean = 0.123 mg/L) before lockdown, and from 0.03 to 0.40 mg/L (mean = 0.113 mg/L) after COVID-19 lockdown period.…”
Section: Heavy Metals In Groundwatermentioning
confidence: 99%
“…Like Fe, Mn concentration in groundwater also decreased after COVID-19 lockdown (Figure . 2b). Brindha et al (2020) showed that Mn affects the taste of water, and precipitates in food when used for food preparation and also promotes the growth of algae in reservoirs.…”
Section: Heavy Metals In Groundwatermentioning
confidence: 99%
“…Improving water quality is one of the major environmental challenges worldwide to be solved, since water resources are increasingly scarce due to population growth, climate change and increased demand for water in industrial and agricultural activities [ 1 ]. In addition, the inappropriate disposal of organic and inorganic contaminants combined with disinformation and neglect in the treatment of these compounds can result in irreversible damage to the aquatic environment and, consequently, to humans [ 2 , 3 ]. Dyes, phenolic compounds, metallic ions and micropollutants, such as pesticides and drugs, have all been detected in wastewaters, surface and even drinking water, indicating that the conventional methods used in treatment plants are not optimised for their removal [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of industry, agriculture and urbanization, coupled with multiple human activities that can negatively impact the environment, has led to environmental pollution, and especially the contamination of water bodies [1]. Harmful pollutants in water, such as heavy metal ions, organic pollutants and chemical dyes, represent sources of toxicity and create the potential for bio-accumulation and contamination of the aquatic food chain [2]. The continuous developments in novel techniques and routes that are capable of providing clean and safe water have become a significant interest for scientists [3].…”
Section: Introductionmentioning
confidence: 99%